Fluorochrome‐based definition of naturally occurring Foxp3+ regulatory T cells of intra‐ and extrathymic origin. Issue 12 (23rd September 2014) - Petzold, Cathleen; Steinbronn, Nadine; Gereke, Marcus; Strasser, Ruth H.; Sparwasser, Tim; Bruder, Dunja; Geffers, Robert; Schallenberg, Sonja; Kretschmer, Karsten
Abstract : Under physiological conditions, studies on the biology of naturally induced Foxp3 + Treg cells of intra‐ and extrathymic origin have been hampered by the lack of unambiguous markers to discriminate the mature progeny of such developmental Treg‐cell sublineages. Here, we report on experiments in double‐transgenic mice, in which red fluorescent protein (RFP) is expressed in all Foxp3 + Treg cells, whereas Foxp3‐dependent GFP expression is exclusively confined to intrathymically induced Foxp3 + Treg cells. This novel molecular genetic tool enabled us to faithfully track and characterize naturally induced Treg cells of intrathymic (RFP + GFP + ) and extrathymic (RFP + GFP − ) origin in otherwise unmanipulated mice. These experiments directly demonstrate that extrathymically induced Treg cells substantially contribute to the overall pool of mature Foxp3 + Treg cells residing in peripheral lymphoid tissues of steady‐state mice. Furthermore, we provide evidence that intra‐ and extrathymically induced Foxp3 + Treg cells represent distinct phenotypic and functional sublineages.